Selected demography and socio-economic characteristics of the patients hospitalized following physical violence reporting to base Hospital Matale - Kodithuwakku, K.A.R.I (My University, 2002)
This descriptive cross sectional was carried out to characterized the victims of physical violence attending to base Hospital Matale over of 19 weeks commencing from 13th May 2002.This group included 291 males(81.7) with a maximum number of victims in the age group of 21-30 years (31.3) .There were 65 females victims (18.3) .Compared to the ethnic and religious distribution of the total population of the Matale District, Tamils and Hindus had a significantly high proportion among the victim the while the Sinhales and Buddhisms had a significantly low proportion(p0.001)a majority of the victims (42.3) were involved in elementary occupation while there only 6.2 of the victims having employment above the cervical level. There was no significant difference in the distribution of individual and group violence in relation to the ethnicity and the area of residence